Monitoring of Artificial Nests in Horticultural Ecosystems-Observation of Woodpeckers Ethology - C.A., Mihai; F., Stănică; M.R., Ionescu (KnE Life Sciences, 2017)
In order to increase the integrated protection of horticultural ecosystems by using the biological fight, the installation on artificial nests, is an important measure to help the insectivore birds. In a research program, a number of 166 artificial nets for Passeriformes birds were installed in different ecosystems as parks, botanical gardens and orchards in the South-Eastern part of Romania. During the nests monitoring period an interesting, but in the same time warring phenomenon, was noticed: a certain number of artificial nets were prayed by woodpeckers, especially by Dendrocopos major (Great Spotted Woodpecker). In Romania, all the ten European woodpecker species are nesting, nine being sedentary and one (Jynx torquilla) migratory, leaving the country in autumn. Woodpeckers in general, are very useful in woody plant biological protection, having a predominant insectivore nutrition and being the only one to keep under control the insects that are leaving on, inside and under the trees bark. The paper presents some data regarding the woodpeckers ethology in the studied ecosystems. More research are needed to understand the woodpeckers behaviour and to find protection methods of useful birds' nests against the woodpeckers attack. Keywords: useful birds; Dendrocopos major; Dendrocopos syriacus; Passer montanus; Picus viridis.